Exploitation-Exploration Tensions and Organizational Ambidexterity: Managing Paradoxes of Innovation - Andriopoulos, Constantine; Lewis, Marianne W. (Organization Science, 2009)
Achieving exploitation and exploration enables success, even survival, but raises challenging tensions. Ambidextrous organizations excel at exploiting existing products to enable incremental innovation and at exploring new opportunities to foster more radical innovation, yet related research is limited. Largely conceptual, anecdotal, or single case studies offer architectural or contextual approaches. Architectural ambidexterity proposes dual structures and strategies to differentiate efforts, focusing actors on one or the other form of innovation. In contrast, contextual approaches use behavioral and social means to integrate exploitation and exploration. To develop a more comprehensive model, we sought to learn from five, ambidextrous firms that lead the product design industry. Results offer an alternative framework for examining exploitation-exploration tensions and their management. More specifically, we present nested paradoxes of innovation: strategic intent (profit-breakthroughs), customer orientation (tight-loose coupling), and personal drivers (discipline-passion). Building from innovation and paradox literature, we theorize how integration and differentiation tactics help manage these interwoven paradoxes and fuel virtuous cycles of ambidexterity. Further, managing paradoxes becomes a shared responsibility, not only of top management, but across organizational levels.